PENGARUH INOKULASI CENDAWAN MIKORIZA ARBUSKULA DAN PEMBERIAN ROCK PHOSPHATE TERHADAP SERAPAN P, PERTUMBUHAN, DAN HASIL PADI (Oryza sativa L.) VARIETAS INPARI 19 - - Alfandi; Amran Jaenudin; Yayan Suryana (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2016)
This study aimed to determine: (1) the effect of interaction between Arbuscular Mycorrhizal Fungi inoculation and Rock Phosphate to P Uptake, growth, and yield rice plants (Oryza sativa L.) Varieties Inpari 19, (2) at a dose of Arbuscular Mycorrhizal Fungi and Rock Phosphate uptake P how much produce, growth, and yield the highest rice plants (Oryza sativa L.) Varieties Inpari 19, and (3) the correlation between growth and uptake variables P with rice plants (Oryza sativa L.) Varieties Inpari 19. The experiment was conducted in lowland Ciputih Block Manislor Villages Jalaksana District Kuningan Regency, from March through the month of July 2015. The method used in this study is the experimental method. The experimental design used was a randomized block design (RBD), factorial. The study consisted of two treatment factors, namely Arbuscular Mycorrhizal Fungi and Rock Phosphate were repeated 3 times. The first factor is Arbuscular Mycorrhizal Fungi (C) consists of three levels, namely: C1 (15 kg mycorrhizae), C2 (25 kg mycorrhizae), and C3 (35 kg mycorrhizae). The second factor is Rock Phosphate (R) consists of three levels, namely: R1 (210 kg of rock phosphate fertilizer), R2 (350 kg of rock phosphate fertilizer), and R3 (490 kg of rock phosphate fertilizer). The results showed that: (1) there in a interaction between Arbuscular Mycorrhizal Fungi inoculation and administration of Phosphate Rock to the number of tillers per hill 30 days after planting (DAP), P nutrient uptake, root volume, number of productive tillers, filled grain per panicle, and dry milled grain weight per plot, (2) 25 kg treatment Arbuscular Mycorrhizal Fungi and 350 kg of Rock Phosphate fertilizer showed the best effect on weight of dry milled grain per plot which 6.95 kg/plot or the equivalent of 9.27 tonnes/ha, and (3) there is a significant correlation between the volume of the roots with dry milled grain weight per plot.